Ungarn : Avantgarde im 20. Jahrhundert - Neue Galerie der Stadt Linz, Linz; Baum, Peter; Bajkay, Éva; Baum, Peter; Beke, László; Ex, Sjarel; Gergely, Mariann; Hajdu, István; Hegyi, Lóránd; Honisch, Dieter; Kitschen, Friederike; Maurer, Dora; et al. (Linz : Neue Galerie der Stadt Linz, 1998)
Bak, Imre ; Bortnyik, Sándor ; Brassaï ; Brikás, Ákos ; Deli, Ágnes ; El-Hassan, Róza ; Erdélyi, Gábor ; Feher, Laszlo ; Fényes, Adolf ; Ferenczy, Károly ; Gémes, Péter ; Hencze, Tamas ; Huszar, Vilmos ; Jovanovics, Gyorgy ; Kassak, Lajos ; Kertesz, André ; Klimo, Karoly ; Konok, Tamas ; Korniss, Deszö ; Körösényi, Tamás ; Koszta, Jószef ; Köves, Eva ; Máté, Olga ; Maurer, Dora ; Moholy-Nagy, Laszlo ; Molnar, Vera ; Mulasics, Laszlo ; Nemes-Lamperth, József ; Petö, Hunor ; Rippl-Rónai, József ; Tihanyi, Lajos ; Trombitas, Tamás ; Uitz, Béla ; Vajda, Lajos ; Vasarely, Victor ; Vaszary, János ; Veszelszky, Béla ; Zaborszky, Gabor
biografie
Ungarn : Avantgarde im 20. Jahrhundert, Neue Galerie der Stadt Linz, 27. Aug. - 29. Nov. 1998
Duits
boek
Keywords: Hongarije